Features of the information support system of the State Fiscal Service of Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2018)
The information support system of the agencies of the State Fiscal Service of Ukraine has been characterized; and approaches to the construction of corresponding systems of other countries of the world have been considered. The author has presented propositions for improving the information system of the State Fiscal Service of Ukraine with the purpose to increase the efficiency of the fiscal agencies by the criterion of the time of optimization and processing of information.The author has offered to create a unified state information platform (operating system), which will store integrated databases of all government agencies that carry out tax control in Ukraine. The author believes that the creation and operation of a single information platform will simplify the procedures for the generation and submission of reports in electronic form, conditions will arise for optimizing and systematizing the reporting processes, reducing the processing time for reporting, reducing the human factor impact, and reducing the costs associated with administering the reporting process. Such steps will ensure the confidentiality of information, the reliability of its storage and the continuous operation of the system of e-administration of taxes.Particular attention is paid to the need to create the Information Code of Ukraine, the development and adoption of which will solve the problem of overcoming contradictions in legislative and other normative and legal acts, ensure unity and non-fragmentation of regulatory scope. The structure of the new Code is offered.
Keywords: information; information support; information system; State Fiscal Service of Ukraine; tax information; Tax Code of Ukraine; tax control; electronic document; Information Code of Ukraine